Novel food processing techniques - Vesna Lelas (Mljekarstvo)
Recently, a lot of investigations have been focused on development of the novel mild food processing techniques with the aim to obtain the high quality food products. It is presumed also that they could substitute some of the traditional processes in the food industry. The investigations are primarily directed to usage of high hydrostatic pressure, ultrasound, tribomechanical micronization, microwaves, pulsed electrical fields. The results of the scientific researches refer to the fact that application of some of these processes in particular food industry can result in lots of benefits. A significant energy savings, shortening of process duration, mild thermal conditions, food products with better sensory characteristics and with higher nutritional values can be achieved. As some of these techniques act also on the molecular level changing the conformation, structure and electrical potential of organic as well as inorganic materials, the improvement of some functional properties of these components may occur. Common characteristics of all of these techniques are treatment at ambient or insignificant higher temperatures and short time of processing (1 to 10 minutes). High hydrostatic pressure applied to various foodstuffs can destroy some microorganisms, successfully modify molecule conformation and consequently improve functional properties of foods. At the same time it acts positively on the food products intend for freezing. Tribomechanical treatment causes micronization of various solid materials that results in nanoparticles and changes in structure and electrical potential of molecules. Therefore, the significant improvement of some rheological and functional properties of materials occurred. Ultrasound treatment proved to be potentially very successful technique of food processing. It can be used as a pretreatment to drying (decreases drying time and improves functional properties of food), as extraction process of various components (bioactive food components) or as an emulsifying technique. Pulsed electrical field can be effective in microorganisms destruction, as well as a pretreatment to drying. Some of these techniques has already found its application in food industry of several high industry developed countries.